Governance Innovation Through SiMAWAS: Impact Analysis and Service Enhancement for Strengthening Internal Supervision (Jurnal Bina Praja, 2025)
Digital transformation in the public administration sector has triggered significant changes in governance, with a focus on improving transparency, efficiency, and strengthening public trust through the implementation of e-Government initiatives. In Indonesia, where there is a tendency toward skepticism toward government institutions, the use of digital solutions such as the SiMAWAS platform implemented in Pekalongan Regency aims to strengthen internal oversight. This study proposes the development of an online consultation feature on the SiMAWAS platform to address the limitations of one-way communication that have hitherto constrained productive interaction between the Internal Government Oversight Agency (APIP) and the entities under its supervision. By adopting a design-based research approach based on the Lean User Experience (Lean UX) methodology, this study identifies user needs through documentation studies, informal interviews, and non-participant observations. A high-level prototype was developed using Figma, which includes consultation features, automated route settings, and real-time notification systems. Prototype testing was conducted using the Cognitive Walkthroughs and System Usability Scale (SUS) methods, involving 30 respondents, with an average SUS score of 82.5, indicating a good level of usability. The developed feature enables two-way communication, reduces response time, and enhances transparency through clear and open documentation of interactions. Despite challenges in terms of digital literacy and limited internet access, inclusive user-based design provides a more accessible solution for various user groups. The findings of this study contribute a practical model that can be adapted by local governments to strengthen internal oversight functions by utilizing interactive digital tools, in line with e-Government principles of creating accountability and expanding public engagement.
Keywords: Digital Transformation; E-Government; Internal Oversight; Lean UX